Technology Acceptance of E-Banking Services in an Unnatural Environment - Adeyemi Adepoju; Adebola Adeniji (SEISENSE Journal of Management, 2020)
Purpose- The effect of technology acceptance of e-banking services on satisfaction has been well studied in a system. It is characterized as being in a state of orderliness; however, there is the dearth of study in an unnatural environment, among others.  Design/Methodology- Data were collected through a structured questionnaire from 304 staff of Federal Medical Centre, Owo, Nigeria, that were selected using a random sampling technique. The study hypotheses were assessed with PLS-SEM methodology. Findings- Findings from the study suggest that the customers’ level of perceived usefulness of e-banking pays more considerable attention to the e-banking channels, implying that the usefulness of the technology is considered crucial among the respondents. The SEM results showed that the relationship was positive and significant with small effects. Practical Implications- Customers of e-banking placed emphasis on perceived usefulness in an environment characterized as unnatural.